The Cognemes of the Spanish Language: Towards a Cognitive Modelization of the Submorphemic Units in the Grammatical Words of the Spanish Language - Bottineau, Didier (Public Journal of Semiotics, 2007)
This study will apply to the description of Castilian Spanish grammatical words and morphemes a paradigm of principles which were originally elaborated in morphological analyses of English morphemes (Bottineau 2002, 2003a, 2004, 2006) and then evolved into typological instruments for general morphology. Before starting out on the language it is therefore necessary to summarize the way in which they apply to English. This will be done firstly for lexical units and secondly for grammatical ones. For each, the Spanish data will be set against the English ones.